THERMODYNAMICS OF DEEP GEOPHYSICAL MEDIA - Pankov V.L.; Ullmann W.; Heinrich R.; Kracke D. (My University, 1998)
Analysis of thermodynamic properties of geomaterials at high pressures and temperatures existing in the Earth's interior is presented. The presentation includes a summary on the determination of equations of state based on measured properties of minerals, as well as thermodynamic identities and approximate relations between thermodynamic parameters of the second, third, and in some instances, fourth orders. New expressions were derived for the volume dependences of the coefficient of thermal expansion, the Grüneisen parameter, and the Anderson-Grüneisen parameter. Attention is given to the preparation of the database on mineral properties. Several geophysical estimates, including the lower-mantle properties, were obtained. It was shown that the thermal expansivity decreases 4-5 times along the "hot" mantle adiabat as the pressure increases from 0 to 1.4 Mbar. Under the same conditions, the heat capacity CP drops about 10-15%. The thermal pressure at T > Q is linear in temperature, with an accuracy of 1-3%. The parameter partial2KT/partial Ppartial T at P = 0 for mantle minerals was estimated to be (1-3)cdot 10-4K-1. The acceptable ranges of other lower-mantle parameters are dVT = Kprime - dTge 0.2, qle 0.8, gge 1.1, dTle 3-3.3, and dSle 1.9-2.2. Deviations from the Mie-Grüneisen equation of state are discussed in relation to the volume- and temperature-dependent Grüneisen parameter.
Keywords: THERMODYNAMICS; PROPERTIES OF GEOMATERIALS; LOWER-MANTLE PROPERTIES; EARTH''S INTERIOR